The domestication of the wolf larynx—testing the neural crest connection - Jacob Hansen; Nicole D. S. Grunstra; W. Tecumseh Fitch; Andrew C. Kitchener; Michaela Gumpenberger; Raffaela Lesch (Royal Society Open Science, 2025)
The neural crest domestication syndrome (NCDS) hypothesis suggests that selection pressures for tameness during animal domestication resulted in a down-regulation of neural crest cell migration and proliferation, providing a mechanistic explanation for traits commonly observed across domesticates. We test the viability of this hypothesis via a derived prediction. According to the NCDS hypothesis, neural crest-derived structures should be reduced throughout the entire organism in domesticated variants compared to their wild ancestors. Here, we test this prediction by comparing the larynges of wolves and domestic dogs. Anatomical landmarking of the cricoid and thyroid cartilages confirmed absolutely and relatively shorter vocal folds and smaller larynges in normal (mesocephalic) dogs compared to wolves. Additional quantification of laryngeal anatomy shows that mesocephalic dogs have a smaller cricoid diameter and shape-altered thyroid shields. In addition, we quantify the concrete anatomical changes to the laryngeal cartilages caused by brachycephaly, finding that a flattened thyroid shield and ventral cricoid ring fit the symptomatic descriptions of laryngeal collapse. Our comparison of the larynges of wolves and dogs are consistent with the NCDS-derived prediction and support the validity of the NCDS hypothesis.